I fell in love with hope : a novel - Lancali (Emily Bestler Books/Atria, 2023)
"Against the unforgiving landscape of a hospital, a group of terminally ill patients embraces the joys within their reach: friendship, freedom, rebellion. Each in their own way is broken; each in their own way is stronger for it. In the midst of pain and loss, they find community, even miracles, and together they are determined to reclaim from life what illness has taken from them. But a singular heartbreak has led one to swear off love forever. The risk of experiencing another tragedy feels too great. Yet, in this desolate place where it seems impossible for love to make an appearance, a door opens--and so do hearts."--